Integration Of Norm Activation Theory With Mediators And Moderators To Analyze The Influence Of Personal Norms On The Sustainable Consumer Intention Of MSMEs - A. Endang Astrolina; Yolanda Masnita; Kurniawati Kurniawati (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study addresses a phenomenon that challenges a fundamental assumption of Norm Activation Theory (NAT): that consumer personal norms are not sufficiently strong to consistently drive the intention to support sustainable practices among micro, small, and medium-sized enterprises (MSMEs) in the food and beverage sector. The study aims to examine whether the inclusion of mediating and moderating variables can explain why the relationship between personal norms and consumer intention has appeared weak and inconsistent in previous research. A quantitative explanatory approach was employed, utilizing purposive sampling to select 204 consumers with experience consuming eco-friendly products from MSMEs. Data were analyzed using Partial Least Squares Structural Equation Modeling (SmartPLS 4). The results indicate that personal norms have a significant positive effect on consumer intention (β = 0.167; p = 0.027); however, the strength of this effect relies heavily on two linking mechanisms: perceived behavioral control was found to significantly mediate the relationship, whereas attitude toward behavior did not. Regarding moderation, brand engagement negatively moderated the relationship between personal norms and consumer intention, while social media influence was not found to act as a moderator. These findings suggest that NAT needs to be extended to incorporate conditional cognitive (behavioral control) and relational (brand engagement) mechanisms to more precisely explain how personal norms translate into the intention to support MSME green marketing.